Contractor’s obligations under the turnkey contract on construction of design and survey works - Лукасевич-Крутник, Ірина Степанівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article is devoted to researching of contractor’s obligations under the turnkey contract on construction of design and survey works. The norms of the current Ukrainian legislation, different scientific points of view on the problems and materials of judicial practice are analyzed in the article.